Implementasi Algoritma RVO sebagai Sistem Kendali Gerombolan NPC pada Permainan Action RPG - Fadila, Juniardi Nur; Arif, Yunifa Miftachul (MATICS, 2020)
Abstract— The development of the gaming industry has entered a new phase, the game that was previously used as a means of entertainment, is now widely used as a simulation of a condition in the industry and research. more natural. Especially for a crowd management, much modeling is needed so that the crowd agent can move flexibly without reducing the essence of the crowd's natural movement. In this case, the crowd management case will try to be solved using the RVO algorithm, which with the algorithm, the researcher wants to provide a group of NPCs that can move without colliding with collition obect or other NPCs.